Differences in Age, Stage and Biology of Breast Cancer Presentations at A Private Breast Unit in Johannesburg Before and During The COVID-19 Pandemic - Nazreen Kara; Dominic da Costa; Ella Dougherty; Amina Mahomed; Cassandra Mbanje; Carol-Ann Benn; Dominic van Loggerenberg (European Journal of Breast Health)
Objective: Prior to the 2020 Coronavirus disease 2019 (COVID-19) pandemic, breast cancer (BC) was already a major healthcare concern globally, including in South Africa (SA). The pandemic forced adjustments in BC management and may have also impacted BC presentation characteristics due to social behavior changes. The aim of this study was to describe BC presentations before and during the COVID-19 pandemic at a single facility in SA. Materials and Methods. A retrospective record review was conducted to compare BC presentations before and during the COVID-19 pandemic. The “before” period spanned 11 January 2019 to 31 March 2020 and the “during” period spanned 1 April 2020 to 20 December 2021. The variables analysed included patient age, BC stage at presentation, and tumor biology. Results: A total of 731 patients were seen in the “before” period, and 636 in the “during” period. While there was a significant (p<0.0001) decrease in the mean number of patients who presented to the unit per month during the pandemic, no significant differences were observed in age, BC stage at presentation, or tumor biology between the two study periods. Conclusion: Despite a significant reduction in new BC cases during the COVID-19 pandemic in SA, patient age, BC stage, and tumor biology remained unchanged. The rapid implementation of digital tools for healthcare management is likely to have played an important role in maintaining patient access to care.